MEC3DE - um programa para análise elástica tridimensional com o método dos elementos de contorno - Silva, José Jéferson do Rêgo (1989)
This work deals with linear elastic analysis of three-dimensional problems using the boundary element method coupled with the fundamental solution due to Kelvin. The computer program developed allows for triangular and quadrilateral elements, with constant, linear and quadratic interpolation. In addition, the elements can be continuous, discontinuous or of transition type in any combination. Once the boundary values of tractions and displacements are calculated, internal displacements and stresses are computed including boundary stresses. Finally, some examples are presented and results are compared with alternative numerical or analytical solutions.